###### Advertisements

###### Advertisements

If p ∨ q is true, then the truth value of ∼ p ∧ ∼ q is ______.

###### Advertisements

#### Solution

If p ∨ q is true, then the truth value of ∼ p ∧ ∼ q is** False**.

**Explanation:**

⇒ ∼ (p ∨ q) = ∼ p ∧ ∼ q ......[By D'Morgan's law]

∴ ∼ p ∧ ∼ q = ∼ (p ∨ q)

= ∼ (T) = F.

#### APPEARS IN

#### RELATED QUESTIONS

The negation of p ∧ (q → r) is ______________.

Without using truth tabic show that ~(p v q)v(~p ∧ q) = ~p

Without using the truth table show that P ↔ q ≡ (p ∧ q) ∨ (~ p ∧ ~ q)

If A = {2, 3, 4, 5, 6}, then which of the following is not true?

(A) ∃ x ∈ A such that x + 3 = 8

(B) ∃ x ∈ A such that x + 2 < 5

(C) ∃ x ∈ A such that x + 2 < 9

(D) ∀ x ∈ A such that x + 6 ≥ 9

Write the truth value of the negation of the following statement :

cos^{2} θ + sin^{2} θ = 1, for all θ ∈ R

Rewrite the following statement without using if ...... then.

If a man is a judge then he is honest.

Rewrite the following statement without using if ...... then.

It 2 is a rational number then `sqrt2` is irrational number.

Rewrite the following statement without using if ...... then.

It f(2) = 0 then f(x) is divisible by (x – 2).

Without using truth table prove that:

(p ∨ q) ∧ (p ∨ ∼ q) ≡ p

Without using truth table prove that:

(p ∧ q) ∨ (∼ p ∧ q) ∨ (p ∧ ∼ q) ≡ p ∨ q

Without using truth table prove that:

∼ [(p ∨ ∼ q) → (p ∧ ∼ q)] ≡ (p ∨ ∼ q) ∧ (∼ p ∨ q)

**Using rules in logic, prove the following:**

p ↔ q ≡ ∼(p ∧ ∼q) ∧ ∼(q ∧ ∼p)

Using rules in logic, prove the following:

∼p ∧ q ≡ (p ∨ q) ∧ ∼p

Using rules in logic, prove the following:

∼ (p ∨ q) ∨ (∼p ∧ q) ≡ ∼p

**Using the rules in logic, write the negation of the following:**

(p ∨ q) ∧ (q ∨ ∼r)

Using the rules in logic, write the negation of the following:

p ∧ (q ∨ r)

Using the rules in logic, write the negation of the following:

(p → q) ∧ r

Using the rules in logic, write the negation of the following:

(∼p ∧ q) ∨ (p ∧ ∼q)

Let p ∧ (q ∨ r) ≡ (p ∧ q) ∨ (p ∧ r). Then, this law is known as ______.

**Without using truth table, show that**

p ↔ q ≡ (p ∧ q) ∨ (~p ∧ ~q)

**Without using truth table, show that**

p ∧ [(~ p ∨ q) ∨ ~ q] ≡ p

**Without using truth table, show that**

~ [(p ∧ q) → ~ q] ≡ p ∧ q

**Using the algebra of statement, prove that**

[p ∧ (q ∨ r)] ∨ [~ r ∧ ~ q ∧ p] ≡ p

**Using the algebra of statement, prove that**

(p ∧ q) ∨ (p ∧ ~ q) ∨ (~ p ∧ ~ q) ≡ (p ∨ ~ q)

**Using the algebra of statement, prove that**

(p ∨ q) ∧ (~ p ∨ ~ q) ≡ (p ∨ ~ q) ∧ (~ p ∨ q)

The statement pattern p ∧ ( q v ~ p) is equivalent to ______.

For any two statements p and q, the negation of the expression (p ∧ ∼q) ∧ ∼p is ______

(p → q) ∨ p is logically equivalent to ______

The logically equivalent statement of (p ∨ q) ∧ (p ∨ r) is ______

The negation of p → (~p ∨ q) is ______

(p ∧ ∼q) ∧ (∼p ∧ q) is a ______.

The negation of the Boolean expression (r ∧ ∼s) ∨ s is equivalent to: ______

The logical statement [∼(q ∨ ∼r) ∨ (p ∧ r)] ∧ (q ∨ p) is equivalent to: ______

Without using truth table prove that (p ∧ q) ∨ (∼ p ∧ q) v (p∧ ∼ q) ≡ p ∨ q

Which of the following is not a statement?

Negation of the Boolean expression `p Leftrightarrow (q \implies p)` is ______.

∼ ((∼ p) ∧ q) is equal to ______.

Without using truth table, prove that:

[p ∧ (q ∨ r)] ∨ [∼r ∧ ∼q ∧ p] ≡ p

Without using truth table, prove that : [(p ∨ q) ∧ ∼p] →q is a tautology.

The simplified form of [(~ p v q) ∧ r] v [(p ∧ ~ q) ∧ r] is ______.

Without using truth table prove that

[(p ∧ q ∧ ∼ p) ∨ (∼ p ∧ q ∧ r) ∨ (p ∧ q ∧ r) ∨ (p ∧ ∼ q ∧ r) ≡ (p ∨ q) ∧ r

The statement p → (q → p) is equivalent to ______.

Show that the simplified form of (p ∧ q ∧ ∼ r) ∨ (r ∧ p ∧ q) ∨ (∼ p ∨ q) is q ∨ ∼ p.